2017
DOI: 10.1002/ajim.22756
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and 22‐year all‐cause and coronary heart disease mortality

Abstract: OPA was positively associated with both all-cause and CHD mortality. LTPA was not protective. Among men with CHD, LTPA increased mortality risks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 66 publications
3
37
0
Order By: Relevance
“…Instead, this finding is probably due to so-called healthy worker effect, a form of selection bias were more healthy subjects select into and remain in the most physically strenuous occupations. The presence of this effect was demonstrated in one of the reviewed studies21 and in a previous study on occupational PA and cardiovascular disease incidence 17…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Instead, this finding is probably due to so-called healthy worker effect, a form of selection bias were more healthy subjects select into and remain in the most physically strenuous occupations. The presence of this effect was demonstrated in one of the reviewed studies21 and in a previous study on occupational PA and cardiovascular disease incidence 17…”
Section: Discussionmentioning
confidence: 78%
“…Only one study used relative aerobic workload as an occupational PA exposure measure that inherently accounts for individual fitness level, and this measure was more predictive of mortality than exposure assessment by energy expenditure based on metabolic equivalents of occupational PA alone in the same study 21. These findings suggest that future research on occupational PA needs to take individual fitness into account.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A priori, we decided to stratify by gender because different effects of occupational physical activity on mortality have been reported . The basic model (model 1) was adjusted for age, education (as a proxy for socioeconomic status), marital status, and nationality. In MONICA, we also adjusted for wave.…”
Section: Methodsmentioning
confidence: 99%
“…While the beneficial effects of this type of physical activity on the cardiovascular system are well documented, the literature regarding occupational physical activity is rather inconsistent . Some studies showed health benefits also for occupational physical activity, but other studies showed no significant effects or even reported detrimental health effects . A meta‐analysis suggests that the risk of CVD increases by 10% for moderate and by 24% for high (vs low) levels of occupational physical activity .…”
Section: Introductionmentioning
confidence: 99%